Rapidly Declining SARS-CoV-2 Antibody Titers within 4 Months after BNT162b2 Vaccination - Dong-Ho Jo; Dohsik Minn; Jaegyun Lim; Ki-Deok Lee; Yu-Min Kang; Kang-Won Choe; Kwang-Nam Kim (Vaccines, 2021)
The efficacy and safety of the BNT162b2 vaccine are known, but antibodies are expected to decrease over time after vaccination. We collected blood samples from 104 fully vaccinated health care workers at 3 and 5 weeks after first vaccination and 4 months after second vaccination. Antibody titers and neutralizing antibodies were measured. In our study, both antibody titers and neutralizing antibodies increased significantly at 5 weeks after first vaccination but decreased rapidly at 4 months after second vaccination. Additionally, the results showed a significant decrease regardless of gender or age. Further studies are needed to help determine the interval of SARS-CoV-2 vaccinations.